(untitled) (Medicine Today, 2019)
Introduction: Hypothyroidism is a common medical disorder in the general population especially in women. Over-weight, obesity and dyslipidemia are major public health problem in both developed and developing countries. The present study is an effort to determine the association between hypothyroidism with body mass index (BMI) and dyslipidemia. Materials and Methods: This is a cross sectional descriptive type of observational study of 100 cases of primary hypothyroidism in the age group 15-75 years of both sexes from February 2018 to January 2019 in CMH, Momenshahi. BMI was measured by weight in kg/ height in m2 and lipid profiles were analyzed by semi-automated biochemistry analyzer. Data was analyzed by X-cel. Results: Among 100 cases mean BMI were 28.51±4.52, 75 cases (75%) obese, 16 (16%) over-weight, 8 (8%) normal. Mean serum cholesterol, Triglyceride (TG), high density lipoprotein (HDL) and low density lipoprotein (LDL) are195.1±44.57, 164.49±83.87, 40±3.91 and 122±41 mg/dl respectively. Conclusion: Here data statistically showed primary hypothyroidism is significantly correlated with high BMI and serum cholesterol, TG, LDL levels were also significantly correlated to this disorder. But HDL is not correlated with primary hypothyroidism. Medicine Today 2019 Vol.31(2): 93-97